2015
DOI: 10.1158/1078-0432.ccr-14-0861
|View full text |Cite
|
Sign up to set email alerts
|

PLEKHA5 as a Biomarker and Potential Mediator of Melanoma Brain Metastasis

Abstract: Purpose Approximately 40% of metastatic melanoma patients develop brain metastases. Our purpose was to identify genes aberrantly expressed in melanoma that might be associated with propensity for brain homing. Experimental Design We studied gene expression profiles in a cell line model of brain metastasis (cerebrotropic A375Br cells versus parental A375P cells) and compared them to profiles of patients who developed early brain metastases and who did not. A tissue microarray containing 169 metastatic melanom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 50 publications
5
81
2
2
Order By: Relevance
“…Hypermethylated ITGA7 belongs to the integrin family and is a newly identified tumor suppressor gene that decreases migration and invasion of cancer cells . On the other hand, hypomethylated MMP1 is a potent oncogene promoting metastasis and multi‐drug resistance, and hypomethylated PLEKHA5 facilitates metastasis to the brain . Hence, the functional role of differential methylation within those genes in response to RSV is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylated ITGA7 belongs to the integrin family and is a newly identified tumor suppressor gene that decreases migration and invasion of cancer cells . On the other hand, hypomethylated MMP1 is a potent oncogene promoting metastasis and multi‐drug resistance, and hypomethylated PLEKHA5 facilitates metastasis to the brain . Hence, the functional role of differential methylation within those genes in response to RSV is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This TMA has been previously described (23). Collection of specimens and clinical data was approved by a Yale University Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Age at diagnosis ranged from 20 to 79 (mean-55.4). Follow-up time was up to 187.65 months, mean-31.2 months (23). At diagnosis of stage IV disease, 13% had M1a disease, 29%-M1b and 58%-M1c.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon may indicate a type of ‘leukocytic mimicry’ through which metastatic cells could execute immune expression programs that promote cell migration and invasion. In other studies, additional factors have been identified as potential site-specific mediators of BBB transmigration, including PTGS2, HB-EGF, ST6GALNAC5 (Bos et al, 2009), PLEKHA5 (Jilaveanu et al, 2015), and the serum factor PLGF (Li et al, 2013). It is also becoming apparent that BBB integrity is heterogeneously affected within brain tumors (Lockman et al, 2010; Morikawa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%